Studi Literatur Aktivitas Senyawa Aktif Antibakteri Madu terhadap Methicillin-Resistant Staphylococcus aureus (MRSA) - Herlan Azzahra Salsabila; Suwendar; Sri Peni Fitrianingsih (UNISBA Press, 2022)
Abstract. The incidence of antibiotic resistance can be caused by various things, including the use of antibiotics without a prescription. To overcome this, new alternative antibacterial compounds from natural sources are needed. One of the natural sources in question is honey. The research was conducted using a literature review method from articles and research journals that have been published nationally and internationally. The purpose of this literature study was to examine the antibacterial activity of honey against Methicillin-Resistant Staphylococcus aureus (MRSA) and to determine the active compounds in honey that have activity against these bacteria. The inclusion criteria for data collection were journals in Indonesian or English, fully accessible, and having the keywords